Comparison between the levels of anti mullerian hormone after treatment with clomid versus letrozole in polycystic women: an experimental study - Manal Madany Abdel Qader; Shatha Sami Hussein; Huda Fadhil Jadi (Journal of the Pakistan Medical Association)
Objective: To compare the effect of two ovulation induction drugs on anti-Mullerian hormone level in polycystic women.